Photocrosslinking Activity-Based Probes for Ubiquitin RING E3 Ligases. Issue 1 (16th January 2020) - Mathur, Sunil; Fletcher, Adam J.; Branigan, Emma; Hay, Ronald T.; Virdee, Satpal
Summary: Activity-based protein profiling is an invaluable technique for studying enzyme biology and facilitating the development of therapeutics. Ubiquitin E3 ligases (E3s) are one of the largest enzyme families and regulate a host of (patho)physiological processes. The largest subtype are the RING E3s of which there are >600 members. RING E3s have adaptor-like activity that can be subject to diverse regulatory mechanisms and have become attractive drug targets. Activity-based probes (ABPs) for measuring RING E3 activity do not exist. Here we re-engineer ubiquitin-charged E2 conjugating enzymes to produce photocrosslinking ABPs. We demonstrate activity-dependent profiling of two divergent cancer-associated RING E3s, RNF4 and c-Cbl, in response to their native activation signals. We also demonstrate profiling of endogenous RING E3 ligase activation in response to epidermal growth factor (EGF) stimulation. These photocrosslinking ABPs should advance E3 ligase research and the development of selective modulators against this important class of enzymes. Highlights: Photoactivated activity-based probes developed for large class of ubiquitin E3 ligases ABPs are compatible with divergent RING E3 activation mechanisms Parallelized E3 profiling and detection of growth factor-induced E3 activation Abstract : Activity-based probes (ABPs) are valuable research tools for studying enzyme function. Ubiquitin E3 ligases are one of the largest enzyme families yet ABPs for this enzyme class do not exist. Mathur et al. developed photocrosslinking ABPs for RING E3s and using activity-based proteomics demonstrate activity-dependent readout of diverse E3 activation.